Beyond government size: Types of government intervention and corruption. Issue 4 (12th April 2021) - Bel, Germà
Abstract: Evidence on the relationship between government size and corruption is mixed, and might be misleading, as government size is usually measured by fiscal size. The core hypothesis in this research is that the type of government intervention in the economy – rather than the size of government – is a key explanatory factor for corruption. The empirical analysis disentangles the effects of the two main government tools for intervention: fiscal and regulatory. The main result is that fiscal burden does not present any significant relationship with corruption. In contrast, a consistent and significant positive association is found between regulatory burden and corruption. Furthermore, legal origins and democratic experience contribute to explaining differences in corruption. [Correction added on 22 April 2021, after first online publication: In the Abstract, the word 'quality' has been replaced with 'burden'.]